Development of a new model to engage patients and clinicians in setting research priorities. (January 2014) - Pollock, Alex; George, Bridget St; Fenton, Mark; Crowe, Sally; Firkins, Lester
Objectives: Equitable involvement of patients and clinicians in setting research and funding priorities is ethically desirable and can improve the quality, relevance and implementation of research. Survey methods used in previous priority setting projects to gather treatment uncertainties may not be sufficient to facilitate responses from patients and their lay carers for some health care topics. We aimed to develop a new model to engage patients and clinicians in setting research priorities relating to life after stroke, and to explore the use of this model within a James Lind Alliance (JLA) priority setting project. Methods: We developed a model to facilitate involvement through targeted engagement and assisted involvement (FREE TEA model). We implemented both standard surveys and the FREE TEA model to gather research priorities (treatment uncertainties) from people affected by stroke living in Scotland. We explored and configured the number of treatment uncertainties elicited from different groups by the two approaches. Results: We gathered 516 treatment uncertainties from stroke survivors, carers and health professionals. We achieved approximately equal numbers of contributions; 281 (54%) from stroke survivors/carers; 235 (46%) from health professionals. For stroke survivors and carers, 98 (35%) treatment uncertainties were elicited from the standard survey and 183 (65%) at FREE TEA face-to-face visits. This contrasted with the health professionals for whom 198 (84%) were elicited from the standard survey and only 37 (16%) from FREE TEA visits. Conclusions: The FREE TEA model has implications for future priority setting projects and user-involvement relating to populations of people with complex health needs. Our results imply that reliance on standard surveys may result in poor and unrepresentative involvement of patients, thereby favouring the views of health professionals.